Sleep Quality and Quality of Life Among Older Adults During COVID-19 Pandemic: A Cross-Sectional Study - Abdalla, Pedro P.; Neto, Elzier Sampaio de Queiroz; de Souza Lage, Ana Carolina Silveira; Gomes, Sérgio; de Freitas, Maria das Dores Bezerra; Pedro-Costa, Simão; Machado, Dalmo R. L.; Oliveira, José; Mota, Jorge; Bohn, Lucimere (Current Aging Science, 2022)
Background: Although home confinement reduces the number of SARS-CoV-2 infections, it may negatively impact the psychological and physical health of older adults. Objective: The present study attempted to describe the quality of life (QoL) of older adults before and during the COVID-19 outbreak, focusing on evaluating QoL, physical activity, sitting time, and sleep quality during home confinement. Methods: The present study was conducted in 1,063 older adults (91 % females) enrolled in a Brazilian social program. They were interviewed for QoL (EQ-5D), physical activity (international physical activity questionnaire-short), and sleep quality [Pittsburgh sleep quality index (PSQI)] after 11.6 ± 2.4 weeks of confinement. Logistic regression confirmed changes in QoL. Results: The QoL (86.5 ± 14.7) decreased significantly during confinement (66.0 ± 21.0; P < 0.001), whereas the PSQI global score was 6.8 ± 3.9 points. Older adults spent 18.7 ± 29.8 min/day in moderate to vigorous physical activity, whereas they spent 325.5 ± 144.4 min/day sitting. The PSQI global score [odds ratio (OR): 1.10], sitting time (OR: 1.001), and diseases (OR: 1.23) were significantly associated with low QoL (P < 0.05). Conclusion: Confinement has a deleterious effect on QoL, which is influenced by quality of sleep, sitting time, and disease. Awareness regarding the significance of sleep and physical exercise in older adults can mitigate the damage to their health during confinement.
Keywords: quality of life (QoL)